Fegyverek a középkori igazságszolgáltatásban - Siska, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
This essay presents the weapons in the medieval justice of Hungary. Since they were usually used as symbols as well in the discussed period, it is necessary to involve the cultural history of law. As it will be shown, the weapons were present in all parts of the criminal justice in those days, such as in judicial simbols, criminal devices, means of proof and executors of the sentences.